2014
DOI: 10.3354/ab00546
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between feeding, food deprivation and swimming performance in juvenile grass carp

Abstract: The present study investigated the interrelationships between feeding, food deprivation and swimming performance in juvenile grass carp Ctenopharynodon idellus. Oxygen consumption, as a function of swimming speed, was determined by fitting data to a power function. Speed exponents from oxygen consumption functions were 1.46, 1.23 and 1.91 with time after feeding of 6 h, 2 d and 2 wk, respectively, which indicated that swimming efficiency increased after digestion was complete and decreased with extended food d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…In contrast, food deprivation has been found to impede swimming performance in some fish species (i.e. grass carp, Ctenopharynodon idellus; Cai et al, 2014), while the stress response does not (Gregory and Wood, 1999). This may be a possible explanation for the apparent differences in rates of partial migration; therefore, a focused evaluation of the swimming performance and energetics of individuals from these treatments is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, food deprivation has been found to impede swimming performance in some fish species (i.e. grass carp, Ctenopharynodon idellus; Cai et al, 2014), while the stress response does not (Gregory and Wood, 1999). This may be a possible explanation for the apparent differences in rates of partial migration; therefore, a focused evaluation of the swimming performance and energetics of individuals from these treatments is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that EPOC is lower and recovery more rapid in active fish due to higher cardio-respiratory capacity and the ability to extract oxygen from the environment and distribute it to the tissues more rapidly (Hancock & Gleeson 2008). However, the cost of such a high-capacity cardiorespiratory system is a high expenditure of maintenance energy, as suggested by the higher pre-exercise MO 2 in fasting carps (Cai et al 2014b). In the present study, EPOC, measured over a 60 min recovery period, was 65.20 mg O 2 kg −1 for A. baerii, a relatively low value, indicating a high recovery capability, so that resting pools for fishways can be less extensive.…”
Section: Oxygen Consumption and Swimming Performancementioning
confidence: 98%
“…The range for several cyprinid species is 1.1 to 3.0 (Videler & Nolet 1990). The value of the speed exponent is inversely related to swimming efficiency (Tu et al 2012, Cai et al 2014b). For sturgeons, including A. baerii, the speed exponent is low, indicating a high swimming efficiency.…”
Section: Oxygen Consumption and Swimming Performancementioning
confidence: 99%
See 1 more Smart Citation
“…high water velocity or predation stress). Recently, the competition between digestion and swimming under a postprandial locomotion status has drawn the attention of scientists (Alsop & Wood 1997, Thorarensen & Farrell 2006, Altimiras et al 2008, JourdanPineau et al 2010, Cai et al 2014b). These 2 physiological activities can be performed independentlythe so-called additive meta bolic mode found in fish species such as the common carp Cyprinus carpio (Pang et al 2011) and the European sea bass Dicentrarchus labrax (Alti miras et al 2008, Jourdan-Pineau et al 2010.…”
Section: Introductionmentioning
confidence: 99%